The antibacterial effect of flaxseed extract on selective oral pathogens - comparative in vitro study - Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Subramaniam, Pram Kumar; Mokhtar@Makhtar, Khairani Idah; Mustafa, Nazih Shaban; Abdul Qader, Omar Abdul Jabbar; Zolkofli, Nur Dalila; Wan Hassan, Wan Nor Syahirah; Nameer Shaban, Mustafa; Mohamed Yusoff, Nurul Fatihah (2018)
Introduction: Flaxseed from the flax plant (Linum usitatissimum), which has been cultivated for domestic use since prehistoric times. This study aims to investigate presence of antibacterial effect of flaxseed extract against selected oral pathogen in-vitro. Materials and Methods: This is a laboratory experimental in vitro study using selected oral pathogens cultured in nutrient agar. The pathogens then were inoculated in nutrient based broth and incubation for 24hours. Flaxseed extract efficacy was tested by measurement of the zone of inhibition. The antibacterial activities were compared with streptomycin as positive control and DMSO as negative control. The statistical analysis was done by using SPSS. Results: There is positive antibacterial effects of flaxseed extract against Streptococcus mutans, Streptococcus Pyogenes, Pseudomona Aerigenosa and was comparable in efficacy to that of Streptomycin. Conclusion: This study concludes that flaxseed extract has antibacterial activity ageist selective oral pathogens. The implication of this result will be useful in propagating the use of natural based product as therapeutic drug against the chemicalsynthetic products. This study recommends the use of natural herbal product to have the equal potential while negating the unwanted side effects towards humans’ body.